Tingkat Kepuasan Konsumen Sepeda Motor Dengan Menggunakan Quality Function Deployment (QFD) - Firman Ardiansyah Ekoanindiyo; Novia Asari (Jurnal Ilmiah Dinamika Teknik, 2015)
Consumer demand for products of motorcycles, especially motorcycles matic progressively increasing. So that the emerging new brands that lead the competition in quality and price in the market is getting tighter. Yamaha and Honda are the biggest motor company is now competing in getting the share of motor matic. Yamaha, through its Yamaha M matic able to dominate the market, but his Honda with the Honda B can become a serious contender for Yamaha. So that Yamaha needs to develop products that match the desire or need for consumers to be superior to the Honda. From the research results obtained by the method QFD 32 research variables desired by consumers. Of the 32 positions of the variable M Yamaha and Honda B is almost equal in value the satisfaction of the performance of products in the eyes of consumers. Only there are four variables that product satisfaction score of Honda B ahead of Yamaha M. The variables are fuel-efficient, a key performance magnet, the motor elevation of the land and footrests for the pillion. The overall result of the application of QFD will produce House of Quality (HOQ) which will be information in developing a quality product. To apply this method takes some input from consumers in the form of data about what the interests and perceptions of consumers so that later Yamaha M can make improvements that Yamaha M higher quality. Keywords : Customers need, Customers Satisfaction, Quality Function Deployment (QFD), House of Quality (HOQ)